CMV-Specific T-cell Responses at Older Ages: Broad Responses With a Large Central Memory Component May Be Key to Long-term Survival. (12th February 2017) - Bajwa, Martha; Vita, Serena; Vescovini, Rosanna; Larsen, Martin; Sansoni, Paolo; Terrazzini, Nadia; Caserta, Stefano; Thomas, David; Davies, Kevin A.; Smith, Helen; Kern, Florian
Summary: CMV-specific T-cell responses expand in older people with response size differences seeming larger when single rather than multiple T-cell functions are measured. The oldest old recognize the most CMV proteins and display an unexpectedly large central memory CD4 T-cell compartment. Abstract: Cytomegalovirus (CMV) infection sometimes causes large expansions of CMV-specific T cells, particularly in older people. This is believed to undermine immunity to other pathogens and to accelerate immunosenescence. While multiple different CMV proteins are recognized, most publications on age-related T-cell expansions have focused on dominant target proteins UL83 or UL123, and the T-cell activation marker interferon-γ (IFN-γ). We were concerned that this narrow approach might have skewed our understanding of CMV-specific immunity at older ages. We have, therefore, widened the scope of analysis to include in vitro–induced T-cell responses to 19 frequently recognized CMV proteins in "young" and "older" healthy volunteers and a group of "oldest old" long-term survivors (>85 years of age). Polychromatic flow cytometry was used to analyze T-cell activation markers (CD107, CD154, interleukin-2 [IL-2], tumor necrosis factor [TNF], and IFN-γ) and memory phenotypes (CD27, CD45RA). The older group had, on average, larger T-cell responses than the young, but, interestingly, response size differences were relatively smaller when all activation markers were considered rather than IFN-γ or TNF alone. The oldest old group recognized more proteins on average than the other groups, and had even bigger T-cell responses than the older group with a significantly larger central memory CD4 T-cell component.